Complex Numeral Expressions: A Plea for Grafts. (30th March 2015) - Meinunger, André
Abstract: Grafting is a syntactic device developed and defended by van Riemsdijk (2000 and subsequent work) by which two independent input trees are connected via external remerger of internal elements, thus sharing a constituent. Grafting clearly violates standard assumptions about phrase structure. Still, several structures found in natural language are best analyzed in terms of grafting. The present paper discusses one such construction: complex numerals. It shows that the characteristic multidominance of grafting explains the word order, case assignment, plural, paucal, and singular distribution associated with complex numeral combinations better than a coordination approach and is more compatible with more number (or counting) systems found in the world's languages.